Immunization of Pigs with Recombinant Plasmids Containing Genes of Ubiquitinated p30, p54 and CD2v Proteins of African Swine Fever Virus - Imatdinov Almaz R (Sciendo, 2020)
Three recombinant plasmid constructs, expressing chimeric proteins containing human ubiquitin fused to an ectodomain of one of the potentially protective proteins (p30, p54 and CD2v) of the attenuated MK-200 strain of African swine fever virus (ASFV), were created as potential inductors of specific antiviral cellular immunity. Three-time immunization of pigs with the mixture of these plasmids led to the formation of virus-specific cytotoxic T-lymphocytes (CTL), but did not induce production of virus-specific antibodies. After challenge with the homologous parental virulent ASFV strain M-78 at a dose of 103 HAD50, all five animals (four immunized pigs and one naïve) fell between the 4th and 7th days post infection. The obtained results demonstrated that induction of CTL did not protect pigs against challenge with the virulent ASFV. Balanced activation of CTL and antibody-mediated cellular mechanisms should be investigated.